2021
DOI: 10.1007/s11145-020-10107-4
|View full text |Cite
|
Sign up to set email alerts
|

Language skills, and not executive functions, predict the development of reading comprehension of early readers: evidence from an orthographically transparent language

Abstract: The simple view of reading proposes that the development of reading comprehension in early elementary school is best predicted by children’s fluent decoding and oral language skills. Recent studies challenge this view and suggest that executive functions should also be included in this theoretical model; however, the empirical evidence is not strong enough to clearly support or refute this hypothesis. In this short-term longitudinal study, we used latent variables to test whether executive functions have direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 55 publications
3
24
0
1
Order By: Relevance
“…This conclusion is supported in some 150 studies, involving individuals ranging from beginning reader to expert, from child to adult, and across poverty level and minority status (Hoover & Tunmer, 2020a; Kilpatrick, 2020). This conclusion is also supported in studies conducted on reading in several different languages (Dolean, Lervåg, Visu‑Petra, & Melby‑Lervåg, 2021). In short, based on what we currently know, the SVR, through the weight of the evidence supporting it, is a valid account of reading capacity that must be accommodated in models of how that accomplishment is achieved.…”
Section: Views Of the Simple View Of Readingsupporting
confidence: 65%
See 1 more Smart Citation
“…This conclusion is supported in some 150 studies, involving individuals ranging from beginning reader to expert, from child to adult, and across poverty level and minority status (Hoover & Tunmer, 2020a; Kilpatrick, 2020). This conclusion is also supported in studies conducted on reading in several different languages (Dolean, Lervåg, Visu‑Petra, & Melby‑Lervåg, 2021). In short, based on what we currently know, the SVR, through the weight of the evidence supporting it, is a valid account of reading capacity that must be accommodated in models of how that accomplishment is achieved.…”
Section: Views Of the Simple View Of Readingsupporting
confidence: 65%
“…But let us consider a recent example of a strong test of this view of EF skills as proximal factors, one that employed multiple measures for each of the critical constructs that were then used to derive latent indices of those constructs. Based on longitudinal data from 184 Romanian children spanning second grade, Dolean, Lervåg, Visu-Petra, and Melby-Lervåg (2021) reported that in their structural equation models, the latent variables of word recognition and language comprehension made significant contributions to reading comprehension, accounting for 92% of its variance, while that for latent EF skills made no additional contribution. They also reported that once word recognition was mastered (which is achieved relatively quickly in the transparent Romanian orthography), language comprehension showed a strong effect on reading comprehension while word recognition and EF skills did not.…”
Section: Second Advance: Dependence and Bridge Skillsmentioning
confidence: 99%
“…First, there be greater uniformity and agreement on the skills different tasks are actually assessing, and similar tasks with similar labels can be used across studies. Second, similarly labeled tasks may help better determine whether certain individual metalinguistic skills contribute to reading comprehension or whether the different metalinguistic skills represent a more general construct that helps explains reading comprehension performance (e.g., Dolean et al, 2021). A review of past investigations of the SVR model suggest this latter notion may be true.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…First, there will be greater uniformity and agreement on the skills different tasks are actually assessing, and similar tasks with similar labels can be used across studies. Second, similarly labeled tasks may help better determine whether certain individual metalinguistic skills contribute to reading comprehension or whether the different metalinguistic skills represent a more general construct that helps explains reading comprehension performance (e.g., Dolean et al, 2021). A review of past investigations of the SVR model suggest this latter notion may be true.…”
Section: Theoretical Implicationsmentioning
confidence: 99%